Detection of TT Virus DNA and GB Virus Type C/Hepatitis G Virus RNA in Serum and Breast Milk: Determination of Mother-to-Child Transmission - Schröter, Matthias (American Society for Microbiology, 2000)
To investigate the vertical transmission of the newly described TT virus (TTV), serum and breast milk samples from 46 women as well as sera from their 47 newborns were examined for the presence of TTV DNA by PCR. TTV DNA was detected in 47.8% (n = 22) of the women. All but one child born to these women were also viremic for TTV from the first sample onward. TTV DNA was found in 73.9% (n = 17) of the breast milk samples derived from TTV viremic mothers. The one TTV-negative child born to a viremic mother remained negative during follow-up, although it was breast-fed. Our data show that TTV is highly effectively transmitted from mothers to their children during pregnancy. Although the majority of breast milk samples from viremic mothers are positive by TTV PCR, there is no need to discourage women from breast-feeding, because most children are TTV viremic even before breast-feeding begins.